Effect of Vitamin A Supplements with Iron Therapy among Adolescent Girls (International Journal of Physiology, 2019)
BackgroundDespite of extensive management programmes for iron deficiency anaemia, it remains a challenge for healthcare professionals. So, there is a requirement of supplementing the conventional therapy with some micronutrients which have a possible role in combating the problems of anaemia. Vitamin A is one of those possible micronutrients.Material and MethodAdolescent girl students from a school who were diagnosed as anaemia were categorised randomly into two interventional groups. Those who were not diagnosed as anaemia formed the third group. In group A, Vitamin A supplementation (2, 00, 000 IU single dose) along with Iron in the form of FeSO4 was given for 100 days. Group B students received only Iron supplementation for the same period. Only placebo was given to the students of group C.ResultsIn group A the mean value for blood haemoglobin improved from 10.128+0.196 gm/dL to 12.216+0.215 gm/dL. The improvement was extremely significant (p